2019
DOI: 10.1016/bs.aecr.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive capacity in ecosystems

Abstract: Understanding the adaptive capacity of ecosystems to cope with change is crucial to management. However, unclear and often confusing definitions of adaptive capacity make application of this concept difficult. In this paper, we revisit definitions of adaptive capacity and operationalize the concept. We define adaptive capacity as the latent potential of an ecosystem to alter resilience in response to change. We present testable hypotheses to evaluate complementary attributes of adaptive capacity that may help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 92 publications
(61 reference statements)
0
49
0
3
Order By: Relevance
“…To stimulate adaptive capacity, Armitage (2007) [51] suggested that the following areas need to be understood: (a) the cross-scale relationships and networks among actors in a system, (b) the existing and evolving power relationships among actors, (c) the intangible resources such as trust that influence and shape collaboration and learning, and (d) the extent to which cultural norms and values are consistent with collective action and collaborative learning. This implies that improving adaptive capacity requires an understanding of the social, organizational, and institutional context [52]. Moreover, efforts to build adaptive capacity need to occur at multiple levels [53], since the effectiveness of these efforts is affected by the interactions among various levels.…”
Section: Farmer Adaptive Capacitymentioning
confidence: 99%
“…To stimulate adaptive capacity, Armitage (2007) [51] suggested that the following areas need to be understood: (a) the cross-scale relationships and networks among actors in a system, (b) the existing and evolving power relationships among actors, (c) the intangible resources such as trust that influence and shape collaboration and learning, and (d) the extent to which cultural norms and values are consistent with collective action and collaborative learning. This implies that improving adaptive capacity requires an understanding of the social, organizational, and institutional context [52]. Moreover, efforts to build adaptive capacity need to occur at multiple levels [53], since the effectiveness of these efforts is affected by the interactions among various levels.…”
Section: Farmer Adaptive Capacitymentioning
confidence: 99%
“…We use "resilience" in the sense of ecological resilience (3)-the ability of a social-ecological system to absorb change without shifting to a new regime with a different set of processes and structures. Adaptive capacity describes the potential a social-ecological system has to alter resilience in response to change and maintain the current socialecological regime; a system with high adaptive capacity is more likely to remain resilient given substantial episodes of change (4). Transformative capacity describes the potential of a social-ecological system to shift to a different, but still productive and socially desirable, regime that is again resilient to disturbance (5).…”
mentioning
confidence: 99%
“…In this context stability and persistence are defined as the regime dynamics that are bound within a basin of attraction . Specifically, alternative regimes are characterized by patterns-process relationships and feedbacks that are relatively stable (Beisner et al, 2003), although variability occurs within a regime when they adapt and cope with disturbances (Gunderson, 2000;Angeler et al, 2019). Such variability is clearly evident in the dynamics of cross-scale patterns within spring and summer regimes (Figure 1), which may reflect adaptive community dynamics within the basins of attraction of spring and summer blooms.…”
Section: Discussionmentioning
confidence: 99%